Pengaruh Earning Per Share (EPS), Price Earning Ratio (PER), Return On Asset (ROA), Dan Return On Equity (ROE) Terhadap Harga Saham Pada Perusahaan Food And Beverage Di Bursa Efek Indonesia Tahun 2015–2018 - Rudi Sulistiono; Subchan Subchan (Jurnal Ekonomi Manajemen Akuntansi, 2022)
The purpose of this study was to examine the effect of Earning Per Share (EPS), Price Earning Ratio (PER), Return On Assets (ROA), and Return On Equity (ROE) on Stock Prices in Food and Beverage Companies on the Indonesia Stock Exchange in 2015 - 2018. In this study, the population is the number of Food and Beverage companies listed on the Indonesia Stock Exchange from 2015-2018, totaling 24 companies. The sample in this research is 14 companies x 4 years of observation = 56 samples using purposive sampling method. The results showed that the t-count value of the t-count Earning Per Share (X1) was 4.114 and the probability value was less than 0.05, which was 0.000. This shows that the variable Earning Per Share (X1) has a significant effect on stock prices. Thus, the first hypothesis in this study is accepted. The t-count value of the Price Earning Ratio (X2) is -1.301 and the probability value is greater than 0.05, which is equal to 0.199. This shows that the variable Price Earning Ratio (X2) has no significant effect on stock prices. Thus, the second hypothesis in this study was rejected. The t-count value of Return On Assets (X3) is equal to 8.366 and the probability value is less than 0.05, which is 0.000. This matter shows that the variable Return On Assets (X3) has a positive effect on stock prices. Thus, the third hypothesis in this study is accepted. The t-count value of Return On Equity (X4) is -1.504 and the probability value is greater than 0.05, which is 0.139. This shows that the variable Return On Equity (X4) has no significant effect on stock prices. Thus, the fourth hypothesis in this study was rejected